2016
DOI: 10.3906/vet-1509-49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capacitating agents on sperm pretreatment during in vitrofertilization for blastocyst production in caprines

Abstract: The present study aimed at comparing the relative efficacy of different capacitating agents used for sperm pretreatment during in vitro fertilization (IVF) and subsequent embryo development of caprine oocytes. In experiment 1, the effect of different concentrations of heparin (0, 20, and 50 µg/mL) on sperm pretreatment for different periods of time (30 and 60 min) was studied. In experiment 2, the dose-dependent effect of calcium ionophore (0, 0.1, 0.2, and 0.5 µM) on sperm pretreatment was assessed. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The use of foetal bovine serum in the incubation medium of sperm has not been common; for this reason, little is known about the effect of FBS on sperm functionality. However, some studies have used FBS as a supplement in sperm incubation and in vitro fertilization (Chen et al., ; Funahashi & Day, ,b; Goel et al., ; González‐Fernández et al., ; Karimi et al., ; Keskintepe et al., ; Leibfried‐Rutledge et al., ; Tian et al., ; Yang et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of foetal bovine serum in the incubation medium of sperm has not been common; for this reason, little is known about the effect of FBS on sperm functionality. However, some studies have used FBS as a supplement in sperm incubation and in vitro fertilization (Chen et al., ; Funahashi & Day, ,b; Goel et al., ; González‐Fernández et al., ; Karimi et al., ; Keskintepe et al., ; Leibfried‐Rutledge et al., ; Tian et al., ; Yang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the effect of 10% FBS on the functionality of the alpaca sperm was determined. This concentration has been previously used in the sperm incubation medium of other species (Chen et al., ; Funahashi & Day, ,b; Goel et al., ; González‐Fernández et al., ; Kwon et al., ; Yang et al., ). Rizal and Sangadji () observed that the concentration of FBS at 8%, 10% and 12% did not present significant differences in relation to the sperm motility of ram.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations